Can the World Cut Poverty in Half? How Policy Reform and Effective Aid Can Meet International Development Goals - Collier, Paul; Dollar, David (World Bank, Washington, DC, 2014)
More effective development aid could greatly improve poverty reduction in the areas where poverty reduction is expected to lag: Sub-Saharan Africa, Eastern Europe, and Central Asia. Even more potent would be significant policy reform in the countries themselves. The authors develop a model of efficient aid in which the total volume of aid is endogenous. In particular, aid flows respond to policy improvements that create a better environment for poverty reduction and effective use of aid. They use the model to investigate scenarios-of policy reform, of more efficient aid, and of greater volumes of aid-that point the way to how the world could cut poverty in half in every major region. The fact that aid increases the benefits of reform suggests that a high level of aid to strong reformers may increase the likelihood of sustained good policy (an idea ratified in several recent case studies of low-income reformers). The authors find that the world is not operating on the efficiency frontier. With the same level of concern, much more poverty reduction could be achieved by allocating aid on the basis of how poor countries are as well as on the basis of the quality of their policies. Global poverty reduction requires a partnership in which "third world" countries and governments improve economic policy while "first world" citizens and governments show concern about poverty and translate that concern into effective assistance.